Affects as affordances: disability and the genres of the actionable - Hiskes, Andries (Frontiers in Sociology, 2024)
Prominent theorists such as Tobin Siebers, Ato Quayson, and Martha Stoddard Holmes have proposed that disability may not only elicit different affects, such as fear, admiration, or disgust, but have also envisioned different ways in which the relationship between affect and disability is becoming a central concern in considering how disability is ultimately lived through and experienced in social life. This paper supplements the conceptualization of the affect–disability relationship with the conceptual apparatuses of affordances and genre, to offer an account of the actionable. The actionable is proposed as a form of socio-cultural negotiation of the body and the environment out of which opportunities for action—or affordances— arise. Thomas Stoffregen has proposed affordances as being relational-emergent in nature, meaning that affordances refer to the possibilities for action within a particular constellation of elements, while simultaneously not being reducible to the properties of the individual elements. This paper proposes that affect, understood as the bodily capacities to act and be acted upon, may be understood as evoking affordances—opportunities to act or be acted upon. Additionally, the notions of impairment and disability suggest that capacities and the possibilities of action may vary across different bodies. I connect this to the work by Lauren Berlant on genre, who suggests that modes of responsivity to being affected are rooted in generic thinking. Genres act as structuring and historical forms that embed affect in appropriate modes of responsivity within genre conventions. Affordances are subsequently linked to what is deemed a fitting action within a genre. By invoking Berlant’s work, this paper proposes that the actionable opportunities afforded by bodies are preemptively inscribed in genre conventions, and that the concept of the actionable enables an analysis of which actions are deemed appropriate within genres. Because impaired and disabled bodies have a variety of capacities, these bodies may therefore also hold the capacity to disrupt generic expectations and therefore further emphasize the normativity of the presupposed appropriateness of actions.